Creation and manipulation of common functional groups en route to a skeletally diverse chemical library - Cui, Jiayue (National Academy of Sciences, 2011)
We have developed an efficient strategy to a skeletally diverse chemical library, which entailed a sequence of enyne cycloisomerization, [4 + 2] cycloaddition, alkene dihydroxylation, and diol carbamylation. Using this approach, only 16 readily available building blocks were needed to produce a representative 191-member library, which displayed broad distribution of molecular shapes and excellent physicochemical properties. This library further enabled identification of a small molecule, which effectively suppressed glycolytic production of ATP and lactate in CHO-K1 cell line, representing a potential lead for the development of a new class of glycolytic inhibitors.